DIAGNOSTICS OF THE QUALITY OF VOCATIONAL EDUCATION IN THE FIELD OF PHYSICAL CULTURE AND SPORT USING TASKS DEVELOPED WITH REQUIREMENTS OF THE NATIONAL QUALIFICATION SYSTEM - Zadorozhnaya, N.A.; Dubkova, N.V.; Bolotova, I.A.; Domozhilova, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and evaluate the effectiveness of applying a bank of test tasks in the discipline "Hygienic bases of physical culture and sports activities" for diagnosing the quality of vocational education. Methods and structure of the study. A bank of test tasks has been developed and tested for conducting knowledge control in the discipline "Hygienic foundations of physical culture and sports activities" taking into account the requirements for three main professional qualifications in the 2nd year of the bachelor’s degree program at the Lesgaft National State University of Physical Education, Sports and Health. Results and conclusions. It is shown that the proposed diagnostic criteria for assessing the quality of vocational education make it possible to take into account the modern requirements of the development of society and contribute to improving the level of training in the field of physical culture and sports in accordance with the requirements of the national qualifications system.